2019
DOI: 10.1016/j.rmed.2019.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Increase in blood eosinophils during follow-up is associated with lung function decline in adult asthma

Abstract: A B S T R A C TBackground: Asthma is associated with accelerated rate of lung function (FEV 1 ) decline. Objective: To determine predictive factors associated with FEV 1 decline in adult asthma. Methods: A retrospective study was conducted in 229 asthmatics recruited from the University Asthma Clinic of Liege. Subjects had at least two visits with post-bronchodilation (post-BD) FEV 1 and minimum one year between them. A multivariable linear regression analysis was conducted in order to come up with factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 54 publications
6
16
0
Order By: Relevance
“…Therefore, lung function decline requires the association of a marked airway narrowing and eosinophilic inflammation. Studies have recently found an association between higher blood/ sputum eosinophil counts and lung function decline among asthmatics, [8][9][10][11][12][13] which, according to our results, may affect approximately 23% of patients receiving a step-5 treatment associated with omalizumab. It is not clear how eosinophilic inflammation affects lung function decline.…”
Section: F I G U R Esupporting
confidence: 76%
See 3 more Smart Citations
“…Therefore, lung function decline requires the association of a marked airway narrowing and eosinophilic inflammation. Studies have recently found an association between higher blood/ sputum eosinophil counts and lung function decline among asthmatics, [8][9][10][11][12][13] which, according to our results, may affect approximately 23% of patients receiving a step-5 treatment associated with omalizumab. It is not clear how eosinophilic inflammation affects lung function decline.…”
Section: F I G U R Esupporting
confidence: 76%
“…[3][4][5][6] Furthermore, other researches assert that failing to reduce eosinophilic inflammation (BE and/or FENO) significantly influences asthma control and lung function improvement. 10,16,17 Hence, the reversibility test may be a marker of reduced response because it may reflect a persistent eosinophilic airway inflammation suggesting possible different treatments as anti-eosinophilic therapies. RAO+ subjects showed a lower post-treatment FEV 1 , confirming what observed by other studies.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…The high incidence and high recurrence rate of BA not only bring a heavy economic burden to patients but also seriously affect their quality of life. If symptoms persist, patients may have asthma exacerbations [5,6], lung function decline [7], and pathological bronchial wall narrowing [8], which may cause psychological depression [9] and eventually lead to limited daily activities and even death [10].…”
Section: Introductionmentioning
confidence: 99%